Evaluation of staff attitudes about patients\' safety culture in Noor & Ali Asghar hospitals in Isfahan-2011 - Z Agharahimi; M Mostofi; M Jafari; AR Raesi Ahmad (Tehran University of Medical Sciences, 2012)
Background: Health service providers' attitude profoundly influence quality of patient care and safety, and lead to increase effectiveness, cost controlling and decreasing complaint. This study aims to examine staff attitudes' about patients' safety culture in Noor & Ali Asghar hospitals in Isfahan province. Materials & Methods: The survey was a cross-sectional study and was done in 2011. Data were collected from all the staff groups in hospital (n=106). A standard questionnaire from Agency of Healthcare Research and Quality (AHRQ) with a =79% is used to evaluate staff attitudes' toward different aspects of patients' safety culture. This study used SPSS 16.0 to perform the statistical analysis. Results: The response rate for the survey was 89%. The study revealed that 53.7% of the personnel were not reporting errors in 12 months before. Results showed that the average of staff attitudes' scale toward patients' safety culture was (64±5.28) the highest scale was belong to supervisor/ manager expectations & actions promoting patient safety (72.8±15.8) and the lowest one to handoffs & transitions (56.4±14.8). Conclusions: According to scale of staff attitudes about patients' safety culture and its effect on service quality, doing reengineering of work environment, Patients' Safety Initiatives including personnel collaborative, communication openness about error, designing of education plan and making error reporting should be recommended.